Faktor-faktor yang mempengaruhi nilai perusahaan pada perusahaan manufaktur sektor industri barang konsumsi yang terdaftar di Bursa Efek Indonesia Tahun 2016-2019 - Tina Novianti Sitanggang; Yolanda Angel Sabatani Doloksaribu (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to analyze the effect of Capital Structure (DER), Current Ratio (CR), Net Profit Margin (NPM), and Firm Size (UP) on Firm Value (NP). This research was conducted on manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2016-2019. Data were analyzed using multiple regression models. The study results found that CR and NPM had a significant effect, while DER and UP had no significant effect on firm value.